2013
DOI: 10.1111/lam.12130
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different isolation protocols on detection and molecular characterization of Campylobacter from poultry

Abstract: Significance and Impact of Study: The tracing of Campylobacter through the food chain remains important to control campylobacteriosis in humans. Our study points out that the isolation method used affects the genotypes obtained, and this should be considered as a variant when comparing the results of surveillance studies. AbstractWe determined whether different methods to isolate Campylobacter (including the ISO standard 10272:2006-1) affected the genotypes detectable from poultry, at three points during slau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…This is in contrast to the frequency of recovery observed for the remaining subtypes (Ranks 2, 3 and 4), which collectively decreased from 59.5% of the population recovered by nonenrichment isolation to 37.6% of isolates by enrichment. These results are consistent with studies by and Ugarte-Ruiz et al (2013) in which they assessed the genotype diversity of C. jejuni isolated from poultry samples using a variety of isolation protocols and found method-specific differences in the genotypes and numbers of isolates observed. They concluded that enrichment methods, in particular, limit the "genotypic richness" of the population recovered Ugarte-Ruiz et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is in contrast to the frequency of recovery observed for the remaining subtypes (Ranks 2, 3 and 4), which collectively decreased from 59.5% of the population recovered by nonenrichment isolation to 37.6% of isolates by enrichment. These results are consistent with studies by and Ugarte-Ruiz et al (2013) in which they assessed the genotype diversity of C. jejuni isolated from poultry samples using a variety of isolation protocols and found method-specific differences in the genotypes and numbers of isolates observed. They concluded that enrichment methods, in particular, limit the "genotypic richness" of the population recovered Ugarte-Ruiz et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with studies by and Ugarte-Ruiz et al (2013) in which they assessed the genotype diversity of C. jejuni isolated from poultry samples using a variety of isolation protocols and found method-specific differences in the genotypes and numbers of isolates observed. They concluded that enrichment methods, in particular, limit the "genotypic richness" of the population recovered Ugarte-Ruiz et al, 2013). In contrast to using natural samples for experimentation, our controlled experimental set-up allowed us to examine the nature of these findings more directly owing to the removal of potential confounders when dealing with recovery of isolates from samples of unknown strain composition.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations